Study of Environmental Impact in Tourism Development of Delta Areas, Buton Utara Regency, South East Sulawesi - Vita Kartikasari; Wa Ode Sitti Warsita Mahapati (International Conference on Coastal and Delta Areas, 2015)
International tourism market competition is forcing each country to diversify tourismproducts that uniqueness of each country. Tourism market has shifted from